Asthma and COVID-19: who wins the contested territory of the lower airways? - Fraga, Taís de Lima e (2021)
Among the numerous published studies on COVID-19 in a pandemic year, few listed asthma as a comorbidity, making it therefore difficult to draw any solid conclusions. The respiratory allergy and controlled exposures to allergens are associated with significant reductions in the expression of angiotensin-converting enzyme 2 (ACE2), receptor for SARS-CoV-2 entry into human cells. There is a hypothesis that patients with chronic asthma, due to the type 2 inflammatory profile, may be potentially resistant to developing a severe clinical course of COVID-19. The low IFN-g-mediated response in the respiratory tract of asthmatic patients could limit ACE2 expression in the target cells of SARS-CoV-2 infection. The inflammatory profile of the airways in patients with chronic asthma is mainly related to a Th2 response in type-2 asthma, with production of IL-4, IL-13 and IL-5, presenting antagonistic relationship with pro-inflammatory cytokines such as IFN-g, produced at high levels in severe COVID-19. Published studies, for the most part, are retrospective and may have loss of information or present material with limited possibility for more robust and conclusive analysis. It is important to discuss how patients with atopic or nonatopic asthma seem to protect themselves from new coronavirus infection and how asthma affects COVID-19 and the course of the disease, since there is no increased mortality in asthmatic patients with COVID-19 compared to non-asthmatic patients.